Evaluation of the Content Validity of the COVID-19 Symptoms Daily Diary - Dine J; Guan Y; Milien M; Ervin C; Byrne DD; Brown ML; De Anda C; Norquist JM (Patient Related Outcome Measures)
Jennifer Dine,1 Yanfen Guan,2 Mirline Milien,1 Claire Ervin,1 Dana D Byrne,2 Michelle L Brown,2 Carisa De Anda,2 Josephine M Norquist2 1RTI Health Solutions, Research Triangle Park, Durham, NC, USA; 2Merck & Co., Inc., Rahway, NJ, USACorrespondence: Jennifer Dine, Patient-Centered Outcomes Assessment, RTI Health Solutions, 3040 E Cornwallis Road, Research Triangle Park, Durham, NC, 27709, USA, Email jdine@rti.orgIntroduction: The COVID-19 Symptoms Daily Diary (CSDD) is a patient-reported outcome measure designed to assess the severity of core COVID-19 symptoms in clinical trials. The preliminary version of the CSDD was developed based on regulatory guidance and the hallmark COVID-19 symptoms identified by the CDC. This study aimed to evaluate CSDD content validity, to determine whether it is fit for the purpose of supporting efficacy endpoints in clinical trials of treatments for COVID-19. This research also sought to evaluate the appropriateness of a newly developed Pre–COVID-19 Symptoms Questionnaire.Methods: A targeted literature review was completed to evaluate the relevance of concepts included in the diary and to identify any important symptoms that may have been missing. Hybrid (concept elicitation and cognitive debriefing) semistructured qualitative interviews were then conducted across 3 iterative rounds with 30 adults in the United States recently diagnosed with COVID-19.Results: The CSDD included concepts that were most frequently reported by interview participants, including those identified as most bothersome and most important to treat. During cognitive debriefing, participants described the diary concepts as salient and reported the instructions, recall period, and response options as clear and appropriate. Only 2 of 15 CSDD items were modified across 3 interview rounds; specifically, definitions for the vomiting and diarrhea frequency items were clarified for consistent interpretation and response. Interview participants also reported general ease in understanding and responding to the Pre–COVID-19 questionnaire, with feedback resulting in only minor changes to the reference period and instructions.Conclusion: The findings of the current study provide strong evidence for the content validity of the CSDD and the appropriateness of each of the items assessed. This rigorous evaluation (aligned with regulatory guidance) indicates that the CSDD is fit for the purpose of supporting efficacy endpoints in planned clinical trials evaluating medications for COVID-19 treatment.Keywords: patient-reported outcome measures, COVID-19, qualitative, symptom burden